A Review of Palm Oil Biomass as a Feedstock for Syngas Fuel Technology (Jurnal Teknologi (Sciences & Engineering), 2015)
Fossil fuel as the world dominated energy source is depleting and posing environmental issue. Therefore, Synthesis gas (or syngas) which serve environmental clean fuel characteristic is expected to play a major role as one of the potential renewable energy in the future. Syngas, produced from solid feedstock (such as biomass, coal, refinery residual, organic waste and municipal waste) via gasification process can be used directly as fuel for power generation. Besides, syngas also acts as key intermediary to produce transport fuel depending on their quality. The chosen feedstock for syngas production determines the composition and heating value of the syngas produced and hence will be reviewed in general. This paper then review critically palms biomass as the potential source of feedstock for syngas production, as it is widely accessible in the context Malaysia. Palm biomass presents a solution that is sustainable and eco-friendly that is yet to be fully capitalized in the palm oil industry.Â  Some of the palm biomass including oil palm frond (OPF), empty fruit bunch (EFB) and palm kernel shell (PKS) are identified to contain high heating value which indicate their potential use as solid biomass feedstock for syngas production.